Anarchy in the UK('s most famous fortress): comradeship and cupidity in Gibraltar and neighbouring Spain, 1890-1902 - Grocott, Chris A.; Stockey, Gareth; Grady, Jo (Taylor & Francis, 2015)
This article is the first to investigate the growth of anarchist ideology and tactics in Gibraltar and the surrounding Spanish region, the Campo de Gibraltar, in the period 1890-1902. We draw upon hitherto unused material from both The National Archives in London and the Gibraltar Government Archives. By doing so, we demonstrate that during this period Gibraltarian and Spanish workers came together, not only to defend and advance their interests by direct action, such as strikes and attacks on employers, but also to advance educational and social causes too. Indeed, by 1898-9 the appeal of this movement was so strong that an attempt by the British Social Democratic Federation to establish a more constitutionalist approach to industrial relations failed. By 1902, the power of anarchist movements and tactics concerned employers in Gibraltar so greatly that they engineered a lock-out – styled a general strike by local workers – and successfully smashed the organising power of the local movement. Meanwhile, on the Spanish side of the frontier a massacre engineered by the local Spanish authorities resulted in the deaths of a number of activists and a hiatus in the movement that would last until the Great War of 1914-18.